Açai neither stains nor alters the mechanical surface properties of nanofill composite resin in vitro (Research, Society and Development, 2023)
The objective of the present laboratory-quantitative in vitro study is to evaluate the effect of açai on the color, hardness, and roughness of a nanofill composite resin. The samples were randomly assigned into three groups according to the chemical degradation (n=25): artificial saliva (control, pH 7.0) and açai sorbet (pH 3.8) and açai juice (pH 4.9). Colour (CIELa*b* scale), surface roughness (Ra), and surface hardness (SH) outcomes were analysed at baseline and after degradation. The specimens were subjected to 3 daily immersions (6 ml, 15 minutes) during 14 days at 37°C. The interval between each soak was 30 minutes. Specimens were washed with distilled water before placed in fresh saliva. After the third soak in a day, they were kept in fresh saliva overnight.  ΔE* values were 1.88 for saliva/sorbet and 2.2 for juice (p=0.017). Of the solutions, only juice reduced the L* and increased a* values (p0.05) for hardness and roughness. The mechanical surface properties of nanofill composite resin were not changed by açai. Thus, there is no need to discontinue the consumption of açai for patients with nanofill composite resin restorations.